Implementation of Shortest Path Finding using Dijkstra’s Algorithm : https://doi.org/10.69692/SUJMRD100118 - Kounlaxay , Kalaphath; Simmavong, Southeva; Manivanh, Vialakone; Thongphet, Somchith; Sengdala, Sinlapaxay; Meksavanh, Bounhome (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Dijkstra's algorithm is one of the algorithms that can be used in the shortest path determination process. Therefore, this research aims to create a simulation to implement how Dijkstra’s Algorithm (DA) was used to find the Shortest Path (STP) to travel through any vertex or node by distance vertex and previews vertex and executed or calculated the minimum cost of each edge. The simulation was created based on the shortest route between the source node and the distance node. We have designed the model of pathfinding based on the real location of each city in the northern part of Laos which the cost of each edge is also based on the actual traffic situation and the experiments show that using Dijkstra's algorithm correctly finds the shortest path from the source node to the destination node.